VD_FINDINFO HC / 2009 / 321 vom 3. April 2009 - VD Tribunal cantonal (2009)
CONDITION DE RECEVABILITÉ, PARTIE CIVILE, DROIT PÉNAL DES MINEURS | 372 al. 1 CPP, 433a al. 2 CPP, 449 CPP, 79 al. 1 let. d LJPM, 81 let. d LJPM